Illumina next generation sequencing data and expression microarrays data from retinoblastoma and medulloblastoma tissues - A.J. García-Chequer; A. Méndez-Tenorio; G. Olguín-López; C. Sánchez-Vallejo; P. Isa; C.F. Arias; J. Torres; A. Hernández-Angeles; M.A. Ramírez-Ortiz; C. Lara; Ma.de.L. Cabrera-Muñoz; S. Sadowinski-Pine; et al. (Data in Brief, 2016)
Retinoblastoma (Rb) is a pediatric intraocular malignancy and probably the most robust clinical model on which genetic predisposition to develop cancer has been demonstrated. Since deletions in chromosome 13 have been described in this tumor, we performed next generation sequencing to test whether recurrent losses could be detected in low coverage data. We used Illumina platform for 13 tumor tissue samples: two pools of 4 retinoblastoma cases each and one pool of 5 medulloblastoma cases (raw data can be found at http://www.ebi.ac.uk/ena/data/view/PRJEB6630).We first created an in silico reference profile generated from a human sequenced genome (GRCh37p5). From this data we calculated an integrity score to get an overview of gains and losses in all chromosomes; we next analyzed each chromosome in windows of 40 kb length, calculating for each window the log2 ratio between reads from tumor pool and in silico reference. Finally we generated panoramic maps with all the windows whether lost or gained along each chromosome associated to its cytogenetic bands to facilitate interpretation. Expression microarrays was done for the same samples and a list of over and under expressed genes is presented here. For this detection a significance analysis was done and a log2 fold change was chosen as significant (raw data can be found at http://www.ncbi.nlm.nih.gov/geo/accession number GSE11488). The complete research article can be found at Cancer Genetics journal (Garcia-Chequer et al., in press) [1]. In summary here we provide an overview with visual graphics of gains and losses chromosome by chromosome in retinoblastoma and medulloblastoma, also the integrity score analysis and a list of genes with relevant expression associated. This material can be useful to researchers that may want to explore gains and losses in other malignant tumors with this approach or compare their data with retinoblastoma.